2012
DOI: 10.1371/journal.pone.0045391
|View full text |Cite
|
Sign up to set email alerts
|

I See What You Mean: How Attentional Selection Is Shaped by Ascribing Intentions to Others

Abstract: The ability to understand and predict others’ behavior is essential for successful interactions. When making predictions about what other humans will do, we treat them as intentional systems and adopt the intentional stance, i.e., refer to their mental states such as desires and intentions. In the present experiments, we investigated whether the mere belief that the observed agent is an intentional system influences basic social attention mechanisms. We presented pictures of a human and a robot face in a gaze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
232
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(279 citation statements)
references
References 41 publications
30
232
9
1
Order By: Relevance
“…According to Wykowska et al [6] an intentional stance is required before people can attribute mental states to agents, and it was shown that beliefs about agency affect the effectiveness of a gaze cue [4,6]. The effects of gaze timing on the onset of imitation in our study are much larger than those observed using a gaze cueing paradigm, which is about 15 ms [4].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…According to Wykowska et al [6] an intentional stance is required before people can attribute mental states to agents, and it was shown that beliefs about agency affect the effectiveness of a gaze cue [4,6]. The effects of gaze timing on the onset of imitation in our study are much larger than those observed using a gaze cueing paradigm, which is about 15 ms [4].…”
Section: Discussioncontrasting
confidence: 54%
“…Therefore, as emphasized by Scassellati [3] and other researchers [4][5][6], it is crucial to focus on how people naturally adopt an 'intentional stance' and interpret the behaviour of the robot as if it possesses goals, intentions, and beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the robot can learn a C that explains the demonstrations [4], using tools like Inverse Optimal Control (IOC) [1,44,60]. However, extending these tools to higher dimensions is an open problem [44], and recent work focuses on learning costs that make the demonstrations locally optimal [32,38], or on restricting the space of trajectories to one in which optimization is tractable [30].…”
Section: Discussionmentioning
confidence: 99%
“…Following [60], we assume trajectories are separable, i.e. P(ξ X→Y→Z ) = P(ξ X→Y )P(ξ Y→Z ), giving us:…”
Section: A Modeling the Goal Inference I Lmentioning
confidence: 99%
See 1 more Smart Citation